O sindicato que a ditadura queria: o Ministério do Trabalho no governo Castelo Branco (1964-1967) - Nagasava, Heliene Chaves (2015)
This paper attempts to analyze the performance of the Ministry of Labour through the articulation of its ministers with other areas of the state bureaucracy during the Castelo Branco government, for, on the one hand, suppress and purge opinions contrary to the dictatorial regime and, secondly, promote a new policy for workers, the 'New Labour'. The term condensed the idea of the economic area to 'democratize' opportunities, expanding the powers of trade unions, shifting its focus from wage demands for development, in association with the government, of projects and investment programs in the social sectors of indirect productivity. To implement the proposal, each minister had to deal with the pressures arising from the process of reform of labor policy and articulate their personal interests with the duties of the ministry. Arnaldo Sussekind resisted demands for an end to stability, altered the strike law, allowed the fractionation of the 13th salary and paved the way for the implementation of the wage policy. At the same time launched a massive intervention in the unions, whose processes allow a better understanding of the interior of the state bureaucracy, and to notice the arguments used to ward off the boards of unions and question the decision-making within the ministry under the new post-coup social context. Walter Peracchi Barcelos used the ministry as a political springboard, proposing and carrying out repressive actions that guaranteed him political advantages and neglecting projects in the economic area, such as the Fundo de Garantia por Tempo de Serviço, threatening important gains for workers. Finally, Luiz Gonzaga do Nascimento Silva reformulated the Banco Nacional de Habitação and unified welfare, actions that allowed the transfer of powers and state resources to the private sector. The research, therefore, maintains that the Ministry of Labour, after the coup, lost political power within the government for allowing the transfer of its responsibilities to layers of the corporate elite and the military, forcing the unions to modify their communication channels and their claims to adapt to the new context.